Cell suppression problem: A genetic-based approach - Almeida, Maria Teresa (2008)
Cell suppression is one of the most frequently used techniques to prevent the disclosure of sensitive data in statistical tables. Finding the minimum cost set of nonsensitive entries to suppress, along with the sensitive ones, in order to make a table safe for publication, is a NP-hard problem, denoted the cell suppression problem (CSP). In this paper, we present GenSup, a new heuristic for the CSP, which combines the general features of genetic algorithms with safety conditions derived by several authors. The safety conditions are used to develop fast procedures to generate multiple initial solutions and also to recombine, to perturb and to repair solutions in order to improve their quality. The results obtained for 300 tables, with up to more than 90,000 entries, show that GenSup is very effective at finding low-cost sets of complementary suppressions to protect confidential data in two-dimensional tables.(2008).